Successful Conservative Treatment of Emphysematous Pyelonephritis in a Diabetic Patient (Medical Forum Monthly, 2024)
Emphysematous pyelonephritis is an uncommon condition, with severe potentially fatal necrotizing pyelonephritis due to gas producing organisms (generally gram negative bacilli, esp. E. coli, proteus, pseudomonas, enterobacter and klebsiella).It occurs usually in elderly diabetics with poor glycemic control and frequently associated with ureteric obstruction. Though most of the patients still require nephrectomy albeit improvement in medical treatment, we present a case of successful conservative treatment of emphysematous pyelonephritis in a diabetic patient.